Konsep Tasawuf Menurut Jalaluddin Rumi (Analisis Terhadap Karya Fihi Ma Fihi) - Rosliana Rambe, Nur Aisah Simamora, Abrar M. Dawud Faza (Center of Knowledge : Jurnal Pendidikan Dan Pengabdian Masyarakat, 2021)
Sufism is a way or way to get closer to Allah SWT. By practicing the concepts that exist in Sufism. The concepts that exist in Sufism direct humans or Sufis to be as close as possible to Allah SWT. Sufism is also a series of soul experiments in pursuing the path of purification and forging spiritual tarbiyah in humans so that they follow what Allah SWT wants, the universe and the universe. And Sufism is one of the treasures of Islamic scholarship which is always interesting to be used as research material for someone who wants to study Islam, because Sufism is a religious phenomenon (experience and appreciation) that accompanies the development of Islam itself. This type of research is a character study research with a qualitative approach that produces data in the form of arguments about Sufism in a descriptive way with the character concerned. The results of this study indicate that the concept of Sufism according to Jalaluddin Rumi's analysis of (the work of fihi ma fihi) is this book contains 71 chapters, the translation of the original book in Arabic entitled "Kitab Fihi Ma Fihi".